Sealing grain boundary defects in polycrystalline ZIF-8 membranes by graphene oxide coating - Ga Eun Kim; Gyu-Jin Lee; Seoung-Eun Nam; Jinsoo Kim; Sung In Lim; Hyuk Taek Kwon (Journal of Membrane Science Letters)
Here we report that a simple graphene oxide (GO) coating can seal the grain boundary (GB) defects of polycrystalline ZIF-8 membranes and thus improve C3H6/C3H8 separation performance, especially separation factor. The effectiveness of GB defect sealing was investigated in terms of the number of GO coatings, the extent of GB defects in ZIF-8 membranes, and GO coating method (dip-coating under atmospheric pressure vs. dip-coating under vacuum), allowing us to conclude that the strategy can mend ZIF-8 membranes with a wide range of GB defects. Moreover, the GO sealing enhanced the pressure-resistance of a ZIF-8 membrane to some extent. Lastly, the GO-sealed ZIF-8 membrane was thermally stable and the intrinsic transport properties of a ZIF-8 membrane was not influenced by the presence of GO.